Fabrication of Microporous Water Filter Using Titanium Dioxide Particles, Silica Particles, and Polyethylene Glycol - Priatama, Aris; Abdullah, Mikrajuddin; Khairurrijal, Khairurrijal; Mahfudz, Hernawan (ITB Journal Publisher, LPPM ITB, 2010)
We report the fabrication of microporous filter for use in filtering both inorganic and organic substances from liquid materials. Titania (TiO 2) anatase was used as the main material for this filter. Polyethylene glycol (PEG) with average molecular weight of 20,000 was also used as additive to control the formation of pores, especially pore sizes. The mixture of titania and PEG was pressed into cylindrical tablet shape at room temperature and then simply heated inside a furnace up to temperature where the PEG decomposed into gas to leave only connected titania particles. The use of titania as base material for the filter allows the organic substances that trapped inside the filter pores to be easily removed by heating up the used filter at above decomposition temperature of the trapped organics. We also made other filter by adding small amount of silica (SiO2) particles to reduce the size of the pores as well as to improve the mechanical strength. We observed that filters containing silica particles, with smaller in size compared to titania, resulted in better mechanical strength, smaller in pore sizes and better filtering results in term of turbidity and dissolved oxygen (DO) content. This method is potential for development of larger scale and cheaper water filters for use in various applications.